2006
DOI: 10.1007/s10582-006-0218-z
|View full text |Cite
|
Sign up to set email alerts
|

Micropinches in plasma flame expanding into vacuum ambient

Abstract: Results of experimental and theoretical studies of plasma parameters in a currentcarrying plasma flame expanding into the vacuum ambient are presented. It is shown that at the initial stage of the discharge burning the short-run beams of multiply charged ions of the cathode material (with mean ion charge state up +9 for Cu) were emitted from the cathode plasma flame. The X-ray pinhole measurements showed that a small-size area of hot electron with a temperature of 100 ÷ 200 eV was formed at a range of about 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The simulation that has been performed earlier showed that formation of a micropinch in a current-carrying plasma jet expanding into an interelectrode gap was due to competition of two processes [8]. The first one was the plasma compression under action of the self magnetic field (rate of the compression was controlled with the discharge current rise rate dI/dt) and the second one was the entraining of the forming neck downstream towards the anode.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation that has been performed earlier showed that formation of a micropinch in a current-carrying plasma jet expanding into an interelectrode gap was due to competition of two processes [8]. The first one was the plasma compression under action of the self magnetic field (rate of the compression was controlled with the discharge current rise rate dI/dt) and the second one was the entraining of the forming neck downstream towards the anode.…”
Section: Discussionmentioning
confidence: 99%